El cambio de sexo y su inscripción en el registro de Identidad Personal. El cambio que el Tribunal Constitucional no se atrevió a aprobar - Eguiguren Praeli, Francisco José (2015)
In this article, the author tries to clarify various aspects of the fundamental right to Personal identity, this with regard to a recent sentence by the Peruvian Constitutional Court which dismissed the claim of a citizen to register in the National Registry of Identification and Civil status his sex change. Also, the autor analyze the arguments that the Court used to make this decision, as well as also used by two of its judges who expressed their disagreement through unique votes. it is point outs that in Peru, as in other countries, there isn’t a law regulating to the registration of sex change. However, for the author this should not limit the Constitutional Court to approve this change.